2016
DOI: 10.1377/hlthaff.2015.0955
|View full text |Cite
|
Sign up to set email alerts
|

Language Services In Hospitals Vary By Ownership And Location

Abstract: Twenty-four million people in the United States have limited English proficiency. They experience barriers to health care because of their inability to communicate effectively with providers. Hospitals are required to provide language services that reflect the needs of people in their communities, but these services are not available systematically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 3 publications
1
40
0
Order By: Relevance
“…28,3033 A recent study found only 68.8% of hospitals in the United States offered language services, including only 74.7% of hospitals characterized as having a high level of need for language services. 34 The cost of hiring interpreters may be considered prohibitive by some health care organizations; however, studies indicate that the estimated cost of providing interpreter services is relatively modest compared with the overall cost of health care and potential benefits, ranging from $4 to $279 per person per year. 35–38 Unfortunately, even when interpreters are readily available, they are underused.…”
Section: Discussionmentioning
confidence: 99%
“…28,3033 A recent study found only 68.8% of hospitals in the United States offered language services, including only 74.7% of hospitals characterized as having a high level of need for language services. 34 The cost of hiring interpreters may be considered prohibitive by some health care organizations; however, studies indicate that the estimated cost of providing interpreter services is relatively modest compared with the overall cost of health care and potential benefits, ranging from $4 to $279 per person per year. 35–38 Unfortunately, even when interpreters are readily available, they are underused.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 24 million people in the United States have limited English proficiency (LEP) [1]. These individuals may have difficulty communicating with health care providers resulting in compromised patient safety and overall poorer health outcomes [1–5].…”
Section: Introductionmentioning
confidence: 99%
“…These individuals may have difficulty communicating with health care providers resulting in compromised patient safety and overall poorer health outcomes [1–5]. However, assistance from professional interpreters has been shown to improve health care outcomes and satisfaction among LEP patients [4, 5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations